Comprehensive Study of Low-Latitude Pi2 Pulsations Using Observations From Multisatellite Swarm Mission and Global Network of Ground Observatories - Thomas, Neethal; Shiokawa, Kazuo; Vichare, Geeta (My University, 2019)
To understand the spatial features of low-latitude Pi2 (6.6–25 mHz) pulsations, acomprehensive study is carried out for the first time using magnetic field measurements from a globalnetwork of low-latitude ground stations (Mlat∶±2◦− 51◦) and the Swarm multisatellites locatedsimultaneously at day and night local times. We have investigated 1-year data from 2014 and found 15Pi2 events with coherent oscillations at satellite and ground. The Pi2 oscillations in the compressional,toroidal, and poloidal components at satellite and H, D, and Z components at ground are investigatedby estimating its coherence, amplitude, and cross phase with respect to midnight ground H variations.The analogous pairs of magnetic field components (satellite compressional with ground H and satellitetoroidal with ground D) above and below the ionosphere are found to have identical phase during night andopposite phase during day, indicating the magnetospheric and ionospheric sources for nighttimeand daytime Pi2s, respectively. During nighttime, Pi2 oscillations identified in the poloidal component arefound to oscillate in phase (out of phase) in the Southern (Northern) Hemisphere. At ground, the phaseand amplitude of H showed significant change near the dawn terminator, whereas H oscillates mostly inphase with respect to midnight ground H at other local times. The oscillations in D component have phasereversal near midnight, dawn, dusk, and noon meridians with opposite hemispheres having oppositephase. These Pi2 characteristics observed globally at ground and at the topside ionosphere suggest that thesources for nighttime and daytime low-latitude Pi2s are oscillating field-aligned currents and ionosphericcurrents, respectively.
Keywords: Ionosphere; Ionospheric current; Swarm multisatellites